Estado actual de la litotricia extracorpórea mediante ondas de choque. - Esteban Fuertes, M.; Hernández Ajubita, H.; Mohamed Mohamed-abdallah, Z.; Ramírez Fernández, J.C.; Resel, Luis; Samblas García, R.; Senovilla Pérez, J.L. (Clínicas Urológicas de la Complutense, 1994)
Sin resumen